A comparative study of the discourse marker types in the body section of the research papers of DLSU students - De Ramos, Jennifer Tan (Animo Repository, 2010)
The study examines the types of discourse markers adult second language (L2) learners in a research writing class most predominantly use given the types of research paper they are required to write. Two Englres (Basic Research) classes at De La Salle University - Manila, each composed of between forty and forty-three students who were assigned to worked in pairs, were selected. Classes were taken from two colleges. From the two research paper classes, thirty papers were collected. The papers were examined on the basis of what discourse markers types are predominantly used in the Body section of the students’ research papers. This study used Hyland and Tse’s Taxonomy of Textual and Interpersonal Metadiscourse (2004) and Halliday and Hasan’s (1976) concept of cohesion. Results reveal that the students from the College of Engineering who are required to write a descriptive research paper use the logical connectives of addition and contrast more than they use the other types of discourse markers. This preference was used because the research paper they are expected to produce is descriptive in nature. Hence the data that the students are expected to come up with need to blend with the existing data that are already available concerning the topic. On the other hand, the students from the College of Liberal Arts, who are expected to turn in an argumentative research paper, show preference for the logical connectives of addition, contrast and consequence because the development of the ideas in the research paper needs to escalate into a level where they are supposed to present their contentions to the arguments that they are putting forth. This study has considerable implications in the kind of teaching materials that L2 learners need to be exposed into given their different fields of specialization